Linking routines to operations capabilities: A new perspective - Peng, David Xiaosong; Schroeder, Roger G.; Shah, Rachna (Journal of Operations Management, 2008)
AbstractA typical approach to studying capabilities in the operations management literature is to assess the intended or realized competitive operational performance and their contribution to business and organizational objectives. While it is crucial to identify the operational performance that helps create competitive advantage, it is equally important to understand the means for delivering the needed performance at the operational level. Drawing on the resource‐based view (RBV), we argue that routines are a critical source of operations capabilities and subsequently investigate operations capabilities by means of their underlying routines. Because a common problem to studying capabilities is the ambiguous and confusing definitions, we conduct an extensive literature review to address the semantic confusion among various definitions of capabilities and delineate it from other related terms. We identify improvement and innovation as two critical plant level capabilities, each consisting of a bundle of interrelated yet distinct routines. We then empirically measure the two capabilities as second‐order latent variables and estimate their effects on a set of operational performance measures. The results suggest that routines form internally consistent bundles which are significantly related to operational performance. This supports our notion of “capabilities as routine bundles” that are difficult to imitate and thus a source of competitive advantage.